211k views
5 votes
Please help. i really dont understand

Please help. i really dont understand-example-1
User Ingyesid
by
6.1k points

1 Answer

5 votes

Answer:


(1)/(2) \ln (y - 10) - (9)/(2) \ln (y + 5)

Explanation:


\ln \sqrt{((y^2 - 100)(y + 5)^9)/(y + 10)} =


= \ln \sqrt{((y + 10)(y - 10)(y + 5)^9)/(y + 10)}


= \ln [(y - 10)(y + 5)^9]^{(1)/(2)}


= (1)/(2) \ln [(y - 10)(y + 5)^9]


= (1)/(2) [\ln (y - 10) - \ln (y + 5)^9]


= (1)/(2) [\ln (y - 10) - 9 \ln (y + 5)]


= (1)/(2) \ln (y - 10) - (9)/(2) \ln (y + 5)

User Jlivni
by
6.6k points